2003
DOI: 10.1038/sj.bjc.6600870
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity to human papillomavirus type 16 L1 virus-like particles in sera from patients with genital cancer and patients with carcinomas at five different extragenital sites

Abstract: A retrospective seroepidemiologic study was performed to examine the association between human papillomaviruses (HPV) 16 infection and carcinomas of the oropharynx, the oesophagus, penis and vagina. Sera were selected from the serum bank from the Antoni van Leeuwenhoek Hospital (Netherlands Cancer Institute) and the Slotervaart Hospital in Amsterdam, the Netherlands. Presence of HPV 16 specific antibody was assessed using HPV 16 L1 capsids. Sera positive for HPV 16 capsid antibody were further tested for antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
44
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 53 publications
(57 reference statements)
3
44
1
Order By: Relevance
“…The risk ratio confidence intervals for the association of HPV 16 and ESCC in the other previous studies were 1.8-11.9, 10 1.0-510, 9 0.5-2.0 11 and 0.3-2.0. 12 Several of these CIs are very wide, indicating unstable risk estimates. All of these CIs overlap those obtained in our study (0.8-3.3).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The risk ratio confidence intervals for the association of HPV 16 and ESCC in the other previous studies were 1.8-11.9, 10 1.0-510, 9 0.5-2.0 11 and 0.3-2.0. 12 Several of these CIs are very wide, indicating unstable risk estimates. All of these CIs overlap those obtained in our study (0.8-3.3).…”
Section: Discussionmentioning
confidence: 99%
“…10 In contrast, the other 2 retrospective studies, both conducted in Europe, found no association between HPV 16 and the risk of ESCC: Lagergren et al found an OR of 1.0 (0.5-2.0), and Van Doornum et al found an OR of 0.8 (0.3-2.0). 11,12 Four of these serologic studies also examined the association between HPV 16 and the risk of esophageal or gastric adenocarcinoma (Table V). None of these studies found a significant association between HPV 16 and these cancers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations